1995
DOI: 10.1136/bmj.310.6989.1225
|View full text |Cite
|
Sign up to set email alerts
|

Community study of role of viral infections in exacerbations of asthma in 9-11 year old children

Abstract: This study supports the hypothesis that upper respiratory viral infections are associated with 80-85% of asthma exacerbations in school age children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
1,422
6
54

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,836 publications
(1,536 citation statements)
references
References 24 publications
(25 reference statements)
54
1,422
6
54
Order By: Relevance
“…If the volume of nasal aspirate was <0.5 mL, rhinorrhoea was induced by spraying 0.1 mL 8 mg . mL -1 histamine (BDH Chemicals, Poole, UK) in 0.9% sodium chloride (made up freshly each day) into each nostril [6]. If the volume of nasal aspirate was still low, swabs of the anterior nares, pharynx and tonsils were taken and immediately immersed in phosphate-buffered saline.…”
Section: Clinical Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…If the volume of nasal aspirate was <0.5 mL, rhinorrhoea was induced by spraying 0.1 mL 8 mg . mL -1 histamine (BDH Chemicals, Poole, UK) in 0.9% sodium chloride (made up freshly each day) into each nostril [6]. If the volume of nasal aspirate was still low, swabs of the anterior nares, pharynx and tonsils were taken and immediately immersed in phosphate-buffered saline.…”
Section: Clinical Specimensmentioning
confidence: 99%
“…These exacerbations are associated with increased airway inflammation and airflow obstruction [4,5]. Studies in childhood asthma have shown that viruses, especially rhinovirus (the cause of the common cold), can be detected by polymerase chain reaction (PCR) in nasopharyngeal samples from a large proportion of these exacerbations [6]. However, the role of rhinovirus in COPD exacerbation has not been evaluated using PCR methods.…”
mentioning
confidence: 99%
“…2010; Johnston et al. 1995) and approximately 60% of asthma exacerbations in adults (Nicholson et al. 1993) and up to 50% of total COPD exacerbations (Seemungal et al.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have clearly demonstrated that severe RSV bronchiolitis is frequently associated with subsequent persistent wheezing, childhood asthma or both (Stein et al, 1999;Gern and Busse, 2002;Henderson et al, 2005;Koponen et al, 2012). HRVs are the most commonly identified viruses involved in wheezing exacerbations in older infants and adolescents (Johnston et al, 1995;Busse and Gern, 1997;Rakes et al, 1999;Wennergren and Kristjansson, 2001;Heymann et al, 2004;Blanken et al, 2013).…”
Section: Introductionmentioning
confidence: 99%